Zwitterionic phosphorylcholine grafted chitosan nanofiber: Preparation, characterization and in-vitro cell adhesion behavior - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN (ELSEVIER SCIENCE BV, 2017)
In this study, zwitterionic phosphorylcholine grafted electrospun chitosan fiber was accomplished in three steps: (1) Azide groups on the chitosan were regioselectively replaced with hydroxyl side group and then the product was electrospun. (2) Chitosan based macroinitiator was prepared using an azide-alkyne click reaction from azide-functionalized electrospun chitosan fiber. (3) Poly(2-methacryloyloxyethyl phosphorylcholine) (MPC) was grafted onto the electrospun chitosan fiber by atom transfer radical polymerization (ATRP) in order to enhance cellular viability and proliferation of 3T3, ECV arid Saos. The structure of surface modified thitosan was characterized by Fourier transform infrared spectrometer (FT-IR) and H-1 nuclear magnetic resonance (H-1 NMR). The surface morphology of the nanofibers was investigated by scanning electron microscope (SEM). In vitro cellular attachment and spreading experiments of 3T3, ECV304 and Saos were performed on electrospun chitosan fibers in the presence and the absence of MPC grafting. Poly(MPC) grafted electrospun fiber showed an excellent performance due to phosphorylcholine groups mimicicing the natural phospholipid. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Phosphorylcholine; Chitosan nanofiber; Surface initiated ATRP; Click chemistry; TRANSFER RADICAL POLYMERIZATION; 2-METHACRYLOYLOXYETHYL PHOSPHORYLCHOLINE; CLICK CHEMISTRY; CHEMICAL-MODIFICATIONS; PHOSPHOLIPID POLYMERS; COLORIMETRIC ASSAY; ELECTROSPUN; SCAFFOLDS; SURFACE; ATRP